2023
DOI: 10.3389/fpls.2023.1112354
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of the laccase (LAC) gene family in Aeluropus littoralis: A focus on identification, evolution and expression patterns in response to abiotic stresses and ABA treatment

Abstract: Laccases are plant enzymes with essential functions during growth and development. These monophenoloxidases are involved in lignin polymerization, and their expression respond to environmental stress. However, studies of laccases in some plants and fungi have highlighted that many structural and functional aspects of these genes are still unknown. Here, the laccase gene family in Aeluropus littoralis (AlLAC) is described based on sequence structure and expression patterns under abiotic stresses and ABA treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 53 publications
(67 reference statements)
2
19
0
Order By: Relevance
“…This finding suggested that the FaETR and FaEIN3/EIN gene family has undergone an expansion in the octoploid strawberry. However, diverse expression patterns were observed between members of the FaETR and FaEIN3/EIN gene family, suggesting that there are different regulatory systems between the members of these gene families affecting their expression levels [52,53]. The ETRs from strawberry, Arabidopsis and tomato in the phylogenetic tree were divided into two subfamilies, which was consistent with previous reports [25,48].…”
Section: Discussionsupporting
confidence: 90%
“…This finding suggested that the FaETR and FaEIN3/EIN gene family has undergone an expansion in the octoploid strawberry. However, diverse expression patterns were observed between members of the FaETR and FaEIN3/EIN gene family, suggesting that there are different regulatory systems between the members of these gene families affecting their expression levels [52,53]. The ETRs from strawberry, Arabidopsis and tomato in the phylogenetic tree were divided into two subfamilies, which was consistent with previous reports [25,48].…”
Section: Discussionsupporting
confidence: 90%
“…It was stated that phytohormones such as ABA, SA, and jasmonic acid are associated with plant cell signalling pathways linked to response of biotic and abiotic stresses [ 61 ]. Key stress signalling pathways and ion transporter genes are controlled by ABA signalling in response to stresses [ 62 ]. Our results disclose that SlE2F/DP genes are probably being in cellular cascades related to ABA.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of genes has undergone changes during evolutionary processes, leading to an increase in the number of exons/introns. Generally, genes with fewer introns go through the editing process and leave the nucleus sooner ( Hashemipetroudi et al., 2023 ; Yaghobi and Heidari, 2023 ). Based on this, the different gene structures may affect the expression pattern of NRAMP genes.…”
Section: Discussionmentioning
confidence: 99%
“…Protein sequences of NRAMP genes from the following species were used in the phylogenetic analysis: Vitis vinifera (Vv), Aegiceras corniculatum (Ac), Solanum tuberosum (St), Populus trichocarpa (Pt), Kandelia obovata (Ko), and Arabidopsis thaliana (At). The MEGA11 (V 6.06) software, available at www.megasoftware.net , was commonly employed to align protein sequences ( Hashemipetroudi et al., 2023 ). The phylogenetic tree was constructed using the neighbor-joining (NJ) method, using 1000 bootstrap replicates.…”
Section: Methodsmentioning
confidence: 99%